An Interview with the First Orthodontist of Nepal - Shrestha, Rabindra Man; Acharya, Asal (Orthodontic Journal of Nepal, 2020)
Born on July 4, 1952, Dr Shambhu Man Singh is the first orthodontist of Nepal. He completed his BDS degree from Kerala University in 1974 and D. Ortho from Royal College of Surgeons Edinburgh in 1989. He started specialist orthodontic service in Kathmandu in 1990. He joined Nepal Army in 1977, where he served for thirty years till 2007 when he retired as a Brigadier General. Dr Singh is an Honorary and Life Member of Orthodontic & Dentofacial Orthopedic Association of Nepal. Besides his glorious involvement in military and civil health services, he is recognized as a humble and gentle person in Nepalese dentistry. Here is an excerpt of the interview between Dr Shambhu Man Singh and the representatives of Orthodontic Journal of Nepal.